A tunable terahertz metamaterial absorber composed of elliptical ring graphene arrays with refractive index sensing application - Qi, Yunping; Zhang, Yu; Liu, Chuqin; Zhang, Ting; Zhang, Baohe; Wang, Liyuan; Deng, Xiangyu; Bai, Yulong; Wang, Xiangxian (Results in physics, 2020)
•Altering Fermi level from 0.2 eV to 0.8 eV, the maximum absorption increases from 10.7% to 49.2%, improved by nearly 5 times, and experiences blueshifts. The maximum absorption is a remarkable high result compared to previous studies.•The variation of incident angle is sensitive to maximum absorption, but insensitive to the resonant wavelength.•For the bilayer graphene structure, the maximum absorption even higher, which has achieved 49.6%, and has a tunable dual-band selective absorption.•This paper also changes the surrounding refractive index to better evaluate the sensing performance of the monolayer structure, producing a structure with the sensitivity up to 14110 nm/RIU. In this paper, we demonstrate a tunable absorber composed of periodically patterned elliptical ring graphene metamaterial arrays. An absorption peak at 53.6μm with the maximum absorption of 49.2% of pure graphene layer has been realized. The effects of different parameters are studied by the Finite Difference Time Domain (FDTD) method. Besides, we simulate the spectra as the surrounding refractive index changes to better evaluate the sensing performance of the structure, producing a structure with the sensitivity up to 14110 nm/RIU. Finally, this paper also analyzes the absorption characteristics of bilayer graphene structure, and has a tunable dual-band selective absorption effect with a maximum absorption of 49.6%. Based on the research, it is more convenient to design the graphene-based optoelectronic devices, biosensor and environmental monitor.